Work Termination During The Covid-19 Pandemic in Indonesia Reviewed from Theory Maṣlaḥah Mursalah - Fitria, Restu; Azzaki, Muhammad Adnan; Mustaqim, Abdul (Nurani, 2022)
This article aims to examine the impact of the Covid-19 pandemic on the sustainability of the economic sector in the form of the phenomenon of termination of employment (PHK) which is increasing in Indonesia. Departing from this phenomenon, this study proposes a problem formulation regarding what is the perspective of ma theory maṣlaḥah, it's mursalah in viewing the termination of employment during the Covid-19 pandemic in Indonesia. This research is library researchby using the approach normative juridical, In answering research questions, this study uses mathematical theory maṣlaḥah mursalah. The results of this study indicate that,itthe occurrence of layoffs (PHK) during the spread of the Covid-19 pandemic Judging from the theoretical objectives maṣlaḥah mursalah, The decision taken by the company in terminating the employment relationship has the aim of company efficiency in order to survive is a situation that occurs beyond the ability of both parties (force majeure). So, if analyzed using the theory of maṣlaḥah, this condition is at the level of division of maṣlaḥah Hᾱjiyyat . Because in this case the steps taken by the company in doing layoffs as an effort to avoid themselves from greater harm if the company is not able to survive but this situation does not have a significant impact on the survival of business actors as classified in the level of Hᾱjiyyat.